Does trust mediate the determinant factor of airplane e-ticket purchase decisions using mobile applications? - Sulistiyawan, Edy; Suharyanto, Suharyanto; Kurniawan, Indra; Arianto, Bisma; Samsiyah, Siti (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2025)
Purpose – This study aims to analyze the influence of information quality, social media marketing, and perceived ease of use on e-ticket purchasing decisions using the tiket.com mobile application mediated by trust. Method – This research applied quantitative methods and a causally associative approach. The population of this study is tiket.com customers in Surabaya, where the number is not known with certainty. Sampling measurement uses the Hair approach, so the number of samples obtained is 130 people. The sampling technique uses purposive sampling with predetermined criteria. Data analysis techniques use partial least squares-structural equality modelling (PLS-SEM) with the SmartPLS statistical tool. Findings – The findings show that quality information, social media marketing, perceived ease of use, and trust positively affect online purchase decisions. Trust can mediate the effect of quality information and social media marketing on online purchase decisions. However, trust cannot mediate the influence of perceived ease of use on online purchase decisions. Implications – Theoretically, this study can strengthen the understanding of the importance of trust in digital consumer behavior. Practically, companies like tiket.com need to focus on presenting accurate information, social media strategies that build trust, and easy and comfortable user experiences.